Appreciative inquiry: An approach for learning and change based on our own best practices - Acosta, A.S.; Douthwaite, Boru (2005)
Since it was conceptualized in the late 1980s as a research methodology and change paradigm, the technique of ‘appreciative inquiry’ (AI) has proved to be highly effective for capturing the positive features of an organization or social system and energizing the members to strive for higher levels of performance. This Brief outlines the basic principles and methods of AI, describes various domains in which it has been undertaken and provides a recent example of its use in a centre affiliated with the Consultative Group on International Agricultural Research (CGIAR).